Structural and computational basis for potent inhibition of glutamate carboxypeptidase II by carbamate-based inhibitors - Barinka, Cyril; Novakova, Zora; Hin, Niyada; Bím, Daniel; Ferraris, Dana V; Duvall, Bridget; Kabarriti, Gabriel; Tsukamoto, Reiji; Budesinsky, Milos; Motlova, Lucia; Rojas, Camilo; Slusher, Barbara S; et al. (Bioorganic & medicinal chemistry, 2019)
A series of carbamate-based inhibitors of glutamate carboxypeptidase II (GCPII) were designed and synthesized using ZJ-43, N-[[[(1S)-1-carboxy-3-methylbutyl]amino]carbonyl]-l-glutamic acid, as a molecular template in order to better understand the impact of replacing one of the two nitrogen atoms in the urea-based GCPII inhibitor with an oxygen atom. Compound 7 containing a C-terminal 2-oxypentanedioic acid was more potent than compound 5 containing a C-terminal glutamic acid (2-aminopentanedioic acid) despite GCPII's preference for peptides containing an N-terminal glutamate as substrates. Subsequent crystallographic analysis revealed that ZJ-43 and its two carbamate analogs 5 and 7 with the same (S,S)-stereochemical configuration adopt a nearly identical binding mode while (R,S)-carbamate analog 8 containing a d-leucine forms a less extensive hydrogen bonding network. QM and QM/MM calculations have identified no specific interactions in the GCPII active site that would distinguish ZJ-43 from compounds 5 and 7 and attributed the higher potency of ZJ-43 and compound 7 to the free energy changes associated with the transfer of the ligand from bulk solvent to the protein active site as a result of the lower ligand strain energy and solvation/desolvation energy. Our findings underscore a broader range of factors that need to be taken into account in predicting ligand-protein binding affinity. These insights should be of particular importance in future efforts to design and develop GCPII inhibitors for optimal inhibitory potency.
Keywords: Catalytic Domain; buněčné linie; vodíková vazba; inhibitory proteas; Prostate-specific membrane antigen; Protein Binding; Quantum Theory; Glutamate carboxypeptidase II; lidé; enzymatické testy; Drosophila; Humans; kvantová teorie; glutamátkarboxypeptidasa II; močovina; Animals; Protease Inhibitors; molekulární modely; Crystal structure; karbamáty; Stereoisomerism; Glutamate Carboxypeptidase II; zvířata; vazba proteinů; Metallopeptidase; Enzyme Assays; katalytická doména; stereoizomerie; Hydrogen Bonding; Cell Line; Carbamates; Urea; Models, Molecular